The Analysis of Amish’s Purity Symbol in “Plain Truth” Novel by Jody Picoult - Falah, A. Ilah Nurul; Yahya, Muhammad; Ibrahim, Ibrahim; Reski Agustiani, Ria (Journal Corner of Education, Linguistics, and Literature, 2024)
The research aims to aanalysis of Amish’s ppurity ssymbols in “Plain Truth” Novel by Jody Picoult. This research used descriptive qualitative method and semiotic approach in analyzing purity symbol. This research used Pierce’s theory and combine with Kennedy’s symbol theory. The instrument of the research is using note taking from the novel. The results of this research prove that there are three different types of symbols in novel Plain Truth,  such as: Character, Object and, Action, while symbol of purity  portray such as: Character explain who commit the purity, like Aaron Fisher, Object explained the purity of the object like beard man, Amish woman outfits, and buggy and horses.